Istorinės atminties akademija - tikslai, nuveikti darbai, veiklos perspektyvos (dr. Aurimo Švedo ir prof. dr. Alfredo Bumblausko pokalbis) - Švedas, Aurimas; Bumblauskas, Alfredas (Lietuvos istorijos studijos, 2007)
Academy of Historical Memory (Istorinės atminties akademija - IAA) is an institution which was initiated by the members of the Department of Theory of History and History of Culture of the Faculty of History of Vilnius University. It was born on the 10th of March, 2006. In the institution’s official website, www.iaa.lt, the members of IAA declare their determination to respond to the tendencies of modern Lithuanian historical culture and to take part in the formation of new models of Lithuanian identity. The first year of activity for the IAA members was very intensive. The reasons of foundation of IAA, its past and future activities, were revealed by the head of the institution prof. Alfredas Bumblauskas who was interviewed by dr. Aurimas Švedas (Research papers "Studies of Lithuanian’s History") on the 8th of June, 2007. During the discussion the following issues were reviewed: the theoretical and methodological principals formulated by Western historiography (Jörn Rüsen, Pierre Nora) which became the catalyst of IAA activity; the main questions which are now raised by the society to historians; the peculiarities of more than one hundred years existing traditional-stereotypical formula of Lithuanianism and the alternatives to the mentioned images, which emerged at the junction of the 20th and 21st centuries as well as the forms of spread of these alternatives.